Knowledge, attitude and application towards fast track surgery among operating room paramedics: a cross-sectional study - Ting Huang; Jingming Wang; Yuanyao Chen; Zhen Ye; Yiwei Fang; Yuze Xia (BMC, 2022)
Abstract Background Fast track surgery has shown its effectiveness to accelerate recovery and gained acceptance in many operations. However, data for paramedics using fast track surgery are limited in China. The aims of our study are to evaluate the knowledge, attitude and application status of fast track surgery in paramedics and to provide suggestions for the better application of fast track surgery. Methods Two Hundred Ninety-one operating room paramedics were investigated by simple random sampling from October 20 to December 20, 2019 time. A self-reported questionnaire was used to collect data with five dimensions: demographic data, cognitive level, knowledge, attitude and application of fast track surgery. Data were analyzed using qualitative and quantitative methods. Results 19.93% of participants never heard fast track surgery and only 3.32% of participants were very familiar with it. Gender (0.702, 95% CI 0.109-1.294), technical title (0.342, 95% CI 0.126-0.558) and awareness of the concept of fast track surgery (0.471, 95% CI 0.165-0.776) had a correlation with the knowledge level of paramedics towards fast track surgery. In terms of attitude towards fast track surgery, gender (− 1.944, 95% CI -3.830- -0.058), age (0.303, 95% CI 0.021-0.585) and knowledge score of fast track surgery (0.426, 95% CI 0.014-0.838) are related. Half of the paramedics believe the most difficult problem in the application of fast track surgery was the lack of multi-team communication and cooperation. Conclusion The knowledge of fast track surgery among paramedics in Wuhan is poor, and some paramedics have a negative attitude towards it. As the attitude is positively correlated with the knowledge, it is necessary to improve the knowledge level of fast track surgery among paramedics in Wuhan.